2012
DOI: 10.1517/17425255.2012.668184
|View full text |Cite
|
Sign up to set email alerts
|

Efflux transporters in the blood–brain interfaces –in vitroandin vivomethods and correlations

Abstract: A more detailed validation of in vitro efflux transporter assays employing primary brain endothelial cultures is needed. This should go along with mapping uptake transporters expressed in the blood-brain interfaces. With the availability of specific inhibitors, utilization of in vivo methods such as brain microdialysis is increasing. Once transporter-humanized mice are available, we may witness a further increase in applications of in vivo methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…; Krajcsi et al . ). For example, intracerebral microdialysis using quinidine as a selective P‐gp substrate has been utilized to investigate P‐gp function at the rat BBB (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Krajcsi et al . ). For example, intracerebral microdialysis using quinidine as a selective P‐gp substrate has been utilized to investigate P‐gp function at the rat BBB (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…With the use of selective drug transporter substrates such as the antiarrhythmic drug quinidine, this technique has been utilized in rats to examine the role of P‐gp at the BBB in vivo (Krajcsi et al . ; Syvänen et al . ; Westerhout et al .…”
mentioning
confidence: 99%
“…On the contrary, rats and mice are ubiquitous, well-established small laboratory animals, readily available to most labs worldwide. Mice also display another advantage over human models as several genetically-modified mice have already been produced, including humanized mice expressing human transporters [20]. Due to their rapid reproduction and maturation to adulthood, they are both good choice models to retrieve primary cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, P-gp and BCRP have an important function in brain. It has been reported that compounds with P app(AP?BL) > 3 Â 10 À6 cm/s easily penetrate the brain, while compounds with P app(AP?BL) < 1 Â 10 À6 -cm/s are unable to pass across the BBB [45]. Our studies showed that P app(AP?BL) values of GA (C15:1) and GA (C17:1) in the MDCK-MDR1 cells were both in the range from 1 Â 10 À6 cm/s to 3 Â 10 À6 cm/s, indicating that GA (C15:1) and GA (C17:1) are hard to penetrate the BBB.…”
Section: Discussionmentioning
confidence: 99%